TEBINBULOQ KONINI O’ZLASHTIRISH BO’YICHA KONNING TEXNOLOGIK MA’LUMOTLARI TAHLILI ASOSIDA KONNING ISH UNUMDORLIGINI RIVOJLANTIRISH TA’MOIYILLARI - Rametullayeva Mehriban Po’latbek qizi (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2024)
In the article, based on the data from the Tebinbulok mine of titanium magnetic ores, located in the Republic of Karakalpakstan, the resulting technology of mine mining (mine mining) for ore extraction, selection of main and auxiliary ones has been developed, equipment, as well as economic aspects.